Carbon‐Based Metal‐Free Catalysts for Electrocatalytic Reduction of Nitrogen for Synthesis of Ammonia at Ambient Conditions. Issue 13 (16th January 2019) - Zhao, Shenlong; Lu, Xunyu; Wang, Lianzhou; Gale, Julian; Amal, Rose
Abstract: The electrocatalytic nitrogen reduction reaction (NRR) is a promising catalytic system for N2 fixation in ambient conditions. Currently, metal‐based catalysts are the most widely studied catalysts for electrocatalytic NRR. Unfortunately, the low selectivity and poor resistance to acids and bases, and the low Faradaic efficiency, production rate, and stability of metal‐based catalysts for NRR make them uncompetitive for the synthesis of ammonia in comparison to the industrial Haber–Bosch process. Inspired by applications of carbon‐based metal‐free catalysts (CMFCs) for the oxygen reduction reaction (ORR) and CO2 reduction reaction (CO2 RR), the studies of these CMFCs in electrocatalytic NRR have attracted great attention in the past year. However, due to the differences in electrocatalytic NRR, there are several critical issues that need to be addressed in order to achieve rational design of advanced carbon‐based metal‐free electrocatalysts to improve activity, selectivity, and stability for NRR. Herein, the recent developments in the field of carbon‐based metal‐free NRR catalysts are presented, along with critical issues, challenges, and perspectives concerning metal‐free catalysts for electrocatalytic reduction of nitrogen for synthesis of ammonia at ambient conditions. Abstract : Emerging carbon‐based metal‐free catalysts have been demonstrated to be promising alternatives to noble metal/metal oxide catalysts for electrocatalytic nitrogen reduction reaction (NRR) at ambient conditions. Recent advances in the development of carbon‐based metal‐free catalysts for electrocatalytic nitrogen fixation are discussed, and the key challenges and future opportunities in this exciting field are highlighted.